Application of Jarome Bruner's Cognitive Theory to the Mathematics Learning Process with an Ethnomathematics Approach as a Strategy to Improve Mathematics Learning Outcomes in Grade 6 Elementary School Students - Kadu, Joko Godo; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
The background of this research arises from the awareness of challenges in understanding mathematical concepts of 6th grade elementary school students. It was found that students' lack of interest in learning and monotonous teaching methods can be the main factors in low mathematics learning outcomes. Therefore, this study was conducted to explore the application of Jerome Bruner's Cognitive Theory with an ethnomathematical approach as an innovative effort to increase the effectiveness of mathematics learning at the elementary school level. This study aims to apply Jerome Bruner's Cognitive Theory in mathematics learning with an ethnomathematical approach as a strategy to improve mathematics learning outcomes in grade 6 elementary school students. Involving students as research subjects, this study uses an experimental method with a pre-test post-test control group design. Data was collected through observation, interviews, and mathematical tests. Data analysis was carried out using related t-tests. The results showed a significant improvement in students' understanding of mathematical concepts after the application of this approach, with the average test score increasing by 15%. The implications of these findings illustrate that the integration of Jerome Bruner's Cognitive Theory and ethnomathematics creates a more contextual and relevant learning environment, facilitating the process of constructing students' mathematical knowledge. The conclusion of this study emphasizes that the application of this approach can be an effective strategy in improving mathematics learning outcomes at the elementary school level, making a conceptual and practical contribution to the development of more innovative mathematics learning.